2017
DOI: 10.1038/s41598-017-03509-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive nano-sized Magnéli phases titanium oxide (TiOx)

Abstract: Despite the strong recent revival of Magnéli phase TiOx as a promising conductive material, synthesis of Magnéli phase TiOx nanoparticles has been a challenge because of the heavy sintering nature of TiO2 at elevated temperatures. We have successfully synthesized chain-structured Magnéli phases TiOx with diameters under 30 nm using a thermal-induced plasma process. The synthesized nanoparticles consisted of a mixture of several Magnéli phases. A post-synthesis heat-treatment was performed to reduce the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 24 publications
1
53
0
1
Order By: Relevance
“…We could not find any work where free‐standing nanoparticles of pure metal‐doped Ti 4 O 7 ‐related Magnéli phases were directly produced. This would allow the determination, at atomic level, of how these complex structures are oriented in the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find any work where free‐standing nanoparticles of pure metal‐doped Ti 4 O 7 ‐related Magnéli phases were directly produced. This would allow the determination, at atomic level, of how these complex structures are oriented in the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Several synthetic methods have also been applied to the production of nanostructured reduced titanium oxides. While most of these techniques reduce TiO 2 to substoichiometric state like MOCVD, laser irradiation or pulsed laser deposition, there are other strategies that produce directly Magnéli phases nanoparticles like the combustion of organometallic precursors using a diffusion flame aerosol or a plasma . All these synthetic routes provide good control over particle size and shape, and are able to produce monodisperse samples besides the incorporation of other elements as dopants.…”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…The results showed that the TiO x nanoparticle-based electrode had a good cyclability and a stable performance aer 1000 cycles during cyclic voltammetry and hence potential to be applied in supercapacitor. 26 The electrochemical conductivity of TiO x nanoparticles was reported to be depending on the composition of the Magnéli phase which constitutes the TiO x . The effect of Magnéli phase composition on the overall rGO/TiO x electrochemical properties is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For all these applications, it is necessary to synthesize single-phase Ti 4 O 7 nanomaterials with a high specific surface area [4]. In previous works, Magnéli phase nanoparticles were synthesized using different methods, such as calcination of titanium ethoxide and polyethylene glycol solution [17], thermal plasma treatment of H 2 TiO 3 under Ar/H 2 [18], sol-gel and calcination [19], sol-gel and vacuum-carbothermic processes [20], pulsed UV laser irradiation [21], and thermal-induced plasma processes [22]. In addition, Zhang O 7 at 1050 • C under a hydrogen atmosphere [23], but the fibers sintered and became submicron chains.…”
Section: Introductionmentioning
confidence: 99%